2010
DOI: 10.1073/pnas.0908278107
|View full text |Cite
|
Sign up to set email alerts
|

Self-organization of the phosphatidylinositol lipids signaling system for random cell migration

Abstract: Phosphatidylinositol (PtdIns) lipids have been identified as key signaling mediators for random cell migration as well as chemoattractant-induced directional migration. However, how the PtdIns lipids are organized spatiotemporally to regulate cellular motility and polarity remains to be clarified. Here, we found that selforganized waves of PtdIns 3,4,5-trisphosphate [PtdIns(3,4,5)P 3 ] are generated spontaneously on the membrane of Dictyostelium cells in the absence of a chemoattractant. Characteristic oscilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
272
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(289 citation statements)
references
References 37 publications
15
272
2
Order By: Relevance
“…It should be emphasized that 2D geometry is essential for understanding dynamics of the observed pattern and their transitions. In earlier models based on one-dimensional geometry (6,15,30,36), a switch of patterns such as reversion of wave propagation along the cell periphery occurs merely by stochastic noise (6). The current study suggests that such a view of pattern transition in many cases could be an oversimplification, because topological charge of the spiral core is robust and cannot simply be flipped by random noise.…”
Section: Phase-map Analysis Reveals Birth and Death Of Spatial Phasementioning
confidence: 80%
See 2 more Smart Citations
“…It should be emphasized that 2D geometry is essential for understanding dynamics of the observed pattern and their transitions. In earlier models based on one-dimensional geometry (6,15,30,36), a switch of patterns such as reversion of wave propagation along the cell periphery occurs merely by stochastic noise (6). The current study suggests that such a view of pattern transition in many cases could be an oversimplification, because topological charge of the spiral core is robust and cannot simply be flipped by random noise.…”
Section: Phase-map Analysis Reveals Birth and Death Of Spatial Phasementioning
confidence: 80%
“…Because the observed wave geometries are generic (26), earlier models of PIP3/F-actin waves in Dictyostelium, whether they are abstract (19) or detailed (6,15), may also be able to capture some of the essential dynamics uncovered in this study. Future studies that include mutant analysis should allow comparison of details that delineate the existing models.…”
Section: Phase-map Analysis Reveals Birth and Death Of Spatial Phasementioning
confidence: 93%
See 1 more Smart Citation
“…In contrast to the spatial distributions of cAMP/cAR1 association and G-protein activation, downstream signaling pathways are activated in an extremely biased manner at the anterior or posterior of the cell (3,4). For example, localized patches of phosphatidylinositol 3,4,5-trisphosphate (PIP 3 ) are generated at the plasma membrane by an intracellular signal transduction excitable network (STEN) and function as a cue to control the pseudopod formation of motile cells (9,10). Because PIP 3 patches have a relatively constant size of a few microns in diameter, this excitable mechanism can ensure a constant output of chemotactic responses over a wide range of concentrations.…”
mentioning
confidence: 99%
“…In stimulated thin neuronal protrusions, it has been observed that slowly diffusing autocatalytic CaMKII kinases exhibit pulsatile compartmentalized activity [36]; a spatially extended bistable system can spontaneously generate subregions, where different steady states dominate [37]. Self-organized foci of activity can generate activating travelling waves [38]. Propagation of waves can give rise to long-lasting cell polarity when the fast-diffusing inhibitor accumulates proportionally to the amount of slow-diffusing activated molecules so that the wavefront can be stalled.…”
Section: State-to-state Transitions In Biological Membrane Systemsmentioning
confidence: 99%